Pharmacogenetics of treatments for pancreatic cancer. (3rd June 2019) - El Hassouni, Btissame; Li Petri, Giovanna; Liu, Daniel S.K.; Cascioferro, Stella; Parrino, Barbara; Hassan, Waqar; Diana, Patrizia; Ali, Asif; Frampton, Adam E; Giovannetti, Elisa
ABSTRACT: Introduction : Despite clinical efforts, pancreatic ductal adenocarcinoma (PDAC) has a dismal prognosis. The scarcity of effective therapies can be reflected by the lack of reliable biomarkers to adapt anticancer drugs prescription to tumors' and patients' features. Areas covered : Pharmacogenetics should provide the way to select patients who may benefit from a specific therapy that best matches individual and tumor genetic profile, but it has not yet led to gains in outcome. This review describes PDAC pharmacogenetics findings, critically reappraising studies on polymorphisms and -omics profiles correlated to response to gemcitabine, FOLFIRINOX, and nab-paclitaxel combinations, as well as limitations of targeted therapies. Further, we question whether personalized approaches will benefit patients to any significant degree, supporting the need of new strategies within well-designed trials and validated genomic tests for treatment decision-making. Expert opinion : A major challenge in PDAC is the identification of subgroups of patients who will benefit from treatments. Minimally-invasive tests to analyze biomarkers of drug sensitivity/toxicity should be developed alongside anticancer treatments. However, progress might fall below expectations because of tumor heterogeneity and clonal evolution. Whole-genome sequencing and liquid biopsies, as well as prospective validation in selected cohorts, should overcome the limitations of traditional pharmacogenetic approaches.